Transfiguration in the poetry of Ahmed Shawky through the poem Abi El Houl (Journal of Human Sciences, 2021)
Intertextuality is a modern term of monetary terms, which belongs to post-structuralism, and it studies the relationships of textual interference between a specific text and other texts, and textual interpolation relationships include citation, inclusion, reference. These interstitial relationships arise through the calling and transfer mechanisms. Intertextuality is a cognitive form that has its methods and mechanisms, and is intended to break down texts, study its reference and its interaction with other texts, and is therefore a term that studies textual interaction and dialogue between texts .in the poetry of Ahmed Shawky through the poem of the Sphinx, as I noticed through my reading of this poem that it is crowded with In this research, I discussed, with God’s power and strength, attunement reclineing on previous texts and filled with summons of history and personalities, until it seemed to me that the texts are calling, and that the summons call for a summons; This led me to study studies on the ground. In the introduction to this paper - before studying the places of intertextuality in the poem of the Sphinx - I examined the meaning of intertextuality in the Arabic language, the concept of intertextuality in the terminology, so that I put the reader in the form of the meaning of intertextuality in the language, and the concept of intertextuality in the terminology, before introducing it to the areas of intertextuality in The poem.